Investigating war crimes in the Former Yugoslavia War 1992-1994 : the United Nations Commission of Experts established pursuant to Security Council Resolution 780 (1992) / M. Cherif Bassiouni. - Bassiouni, M. Cherif, 1937-2017 (Intersentia, 2017)
Following World War Two, the progress towards international accountability and international criminal justice came to a halt as a result of the Cold War. But only three years since the end of the Cold War and forty-five years after the post-WWII prosecutions, the international community was forced to face the ethnic tensions and civil war tearing apart the republics that once comprised the former Yugoslavia. United Nations Security Council Resolution 780 (1992), appointed a Commission of Experts to investigate war crimes and crimes against humanity amounting to violations of international humanitarian law in the territory of the former Yugoslavia and it was expected that the Commission would be the historic link to the post-WWII experiences. Despite the Commission's mandate being the broadest of its kind since Nuremberg, those who opposed its work sought to hamper its success through bureaucratic and political chicanery, including the failure to fund the Commission's work. The investigation into the conflict is detailed in this book including the uncovering of 187 mass graves, the interviewing of 223 victims of rape and sexual assault, and the utilization of prison camps and mass expulsion for the purpose of ethnic cleansing. Along with the author's personal insights and insider anecdotes on the conflict, this book highlights the continuing need for the pursuit of accountability and international criminal justice in a world of thriving bureaucracy and realpolitik. The Commission broke the glass ceiling of realpolitik by fighting the hard battle that lead to the success of its mandate and to the establishment of the International Criminal Tribunal for the Former Yugoslavia. This timely work reminds us all that indeed the past is prologue. About the author M. Cherif Bassiouni served as member and chair of the Commission of Experts established by United Nations Security Council Resolution 780 (1992), whose work is at the center of this book, as well as in twenty-one other UN positions. He is an Emeritus Professor of Law at DePaul University College of Law where he taught for 45 years and was a founding member of the International Human Rights Law Institute. He was also a founder of the Siracusa Institute, formerly the International Institute of Higher Studies in Criminal Sciences, in Siracusa, Italy, where he served as President and now Honorary President. He also served as the Secretary-General, President and Honorary President of the prestigious L'Association Internationale de Droit Pénal. He has authored 30 books and 271 articles, and has edited 44 books and co-authored 5 on International Criminal Law, Comparative Law, Human Rights and U.S. Law. His works have been written in and published in Arabic, Chinese, Farsi, French, German, Hungarian, Italian, Portuguese, Russian and Spanish. His work has been cited by many international courts, including the International Court of Justice and the European Court of Human Rights, as well as the highest courts of nine countries. He has testified before the U.S. Congress 18 times, most recently in July 2014 in connection with the events in Syria. He has been the recipient of numerous honorary degrees and medals from various nations and received the Nomination for the Nobel Peace Prize in 1999.